Analisis Pembuktian Terbalik Pada Tindak Pidana Pencucian Uang (Studi Putusan MA NO. 1454 K/PID.SUS/2011; PUTUSAN MA NO. 537 K/PID.SUS/2014; PUTUSAN MA NO. 336 K/PID.SUS/2015) - Hanifah Azizah; M. Hamdan M. Hamdan; Mahmud Mulyadi; Sunarmi Sunarmi (Mahesa Research Center, 2021)
TPPU (Money Laundering Criminal Act) is regulated in Law 8/2010 on Prevention and Eradication of TPPU. The research was focused on TPPU which corruption as its principle criminal act, Its Law enforcement by using reversal of the burden of proof. The research used juridical normative and descriptive analytic method. The data were gathered by conducting library research and analyzed qualitatively, and the conclusion was drawn deductively, from general to specific. The purposes of this research is to know about the regulation on reversal of the burden of proof in Law on TPPU and the implementation of reversal of the burden of proof in TPPU in the Supreme Court’s Rulings No. 1454 K/ Pid.Sus/2011, No. 527 K/ Pid.Sus/2014, and No. 336K/ Pid.Sus/2015, and how about the obstacles and their solution for reversal of the burden of proof in the case of TPPU. Reversal of the burden of proof should be applied in the level of investigation because TPPU is an extraordinary crime so that extraordinary treatment should also be applied since TPPU has great impact on the State’s economic condition. Therefore, TPPU should have shortcut in its process so that the State’s loss can optimally (effectively and efficiently) be solved.